2024
DOI: 10.3390/ani14020241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Plant Protein Replacement with Insect and Poultry By-Product Meals on the Liver Health and Serum Metabolites of Sea Bream (Sparus aurata) and Sea Bass (Dicentrarchus labrax)

Valeria Donadelli,
Patrizia Di Marco,
Alberta Mandich
et al.

Abstract: The liver health of Gilthead sea bream and European sea bass, fed with fish meal-free diets, including various proportions of plant proteins, as well as insect and poultry by-product meals, was investigated through biochemical and histological analyses using a new liver index (LI) formula. Four isoproteic (45% Dry Matter, DM) and isolipidic (20% DM) diets were compared, including a plant-based control diet (CV) and three other test diets, in which 40% of a plant protein-rich ingredient mixture was replaced wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 99 publications
1
5
0
Order By: Relevance
“…The eviscerated weight of SSH fish was also about 10% higher than that of fish fed CG diet, resulting in relevant commercial implications. No effect on growth performance was noticed in previous experimental studies in which European seabass were fed diets containing 19.5% HIM [18], or gilthead seabream fed diets containing 32.4% HIM and 27.5% PBM [6,24,25]. Thus, the present results confirm the possible use of HIM and PBM in a plant-rich diet for marine species previously observed on an experimental scale [24,25].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The eviscerated weight of SSH fish was also about 10% higher than that of fish fed CG diet, resulting in relevant commercial implications. No effect on growth performance was noticed in previous experimental studies in which European seabass were fed diets containing 19.5% HIM [18], or gilthead seabream fed diets containing 32.4% HIM and 27.5% PBM [6,24,25]. Thus, the present results confirm the possible use of HIM and PBM in a plant-rich diet for marine species previously observed on an experimental scale [24,25].…”
Section: Discussionsupporting
confidence: 88%
“…Although the output of using either HIM or PBM individually is promising, in the frame of sustainable aquaculture intensification, a single protein source is unlikely to meet the essential nutritional requirements of fish and at the same time provide the best quality end-product [10]. During the last five years, the national project "SUstainable fiSH feeds INnovative ingredients-SUSHIN" funded by the AGER2 Network Foundation has evaluated the potential of different unconventional and underused ingredients, tested singly or in combination, as alternative protein sources for aquafeeds, generating new information on the environmental footprint of feeds [12], on fish growth and welfare, and on the nutritional traits of carnivorous fish species economically important for the European aquaculture [22][23][24]. In addition, results obtained under experimental conditions show that feeding gilthead seabream for 18 weeks with diets containing a negligible amount of FM and 40% plant protein replacement by PBM and HIM alone or in combination (30% and 10%, respectively) improved the zootechnical performance of fish and the nutritional characteristics of the fillets, also ensuring physiological well-being and liver health [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the present study, the histological results indicate a favorable liver health status, with a moderate accumulation of lipids in hepatocytes in all fish regardless of diet. In contrast, Donadelli et al [47] recently observed a significant accumulation of hepatocyte lipids associated with marked histological changes that were indicative of an incipient steatotic state in seabass fed a FM-free diet in which 40% of the plant protein was replaced with insect or poultry by-product. These changes appeared to be slightly attenuated when insect meal and PBM were combined to partially replace plant proteins in the diet.…”
Section: Discussionmentioning
confidence: 88%
“…The data available in the literature indicate species-specific differences in the responses to alternative protein-rich feed components. For example, the inclusion of Hermetia illucens and PBM in diets containing no FM resulted in improved gut and liver health in gilthead seabream and rainbow trout [18,24,47].…”
Section: Discussionmentioning
confidence: 99%